Trans-Tasman CGE Modelling: Some illustrative results from the J oani model - Nana, G; Hall, V.B; Philpot, B.P (School of Management Working Papers, 1994)
A two country multi-sectoral computable general equilibrium model for New 2.ealand and Australia is developed and applied to explore issues concerning the effects of the CER-induced tariff reductions and related topics. A comparison with a similar short-run exercise conducted in 1988 records minimal gains from a 1990 starting position as data shows little remaining protection to be removed. The removal of all protection arrangements with respect to imports from outside the CER region results in over 1 % extra GDP in the short run. However, this figure is doubled in both countries in the longer run as further gains from the re-allocation of capital resources amongst the sectors within each country are experienced. In interpreting the model results the critical nature of the assumptions incorporated within the model closure is discussed. Alternative assumptions addressing questions of inter-country capital mobility as well as exchange rate determination are examined.